Fast ReRoute Model with Realization of Path and Bandwidth Protection Scheme in SDN - Oleksandr Lemeshko; Oleksandra Yeremenko; Batoul Sleiman; Maryna Yevdokymenko (Advances in Electrical and Electronic Engineering, 2020)
The paper proposes a Fast ReRoute model with the realization of path and bandwidth protection scheme, which can be used in MPLS for SDN. The task of calculating the set of disjoint primary and backup paths during fast rerouting was reduced to solving the optimization problem of Integer Linear Programming. The advantage of the proposed solution is the possibility of implementing 1:1, 1:2, …, 1:n path protection schemes without the introduction of an additional set of control (routing) variables, which contributes to reducing the dimension of the optimization problem being solved and the computational complexity of its practical implementation. The criterion of optimality of routing solutions contributes to the formation of the primary and backup disjoint paths with the highest possible bandwidth. In this case, the path with the maximum bandwidth will correspond to the primary path, while the remaining paths will be used as backup ones in decreasing order of their bandwidth. The total number of calculated disjoint paths depends on the selected redundancy scheme. The study conducted showed the efficiency and adequacy of the proposed Fast ReRoute model when using various redundancy schemes.